Modelling resource management options: the case of Matang Mangroves Wetlands, Malaysia - Jamal Othman, (Environmental Management Society, Malaysia, 2002)
The management of the Matang mangrove wetlands in Perak, Malaysia is currently under review. To assist decision-makers in determining the optimal management strategy, a Choice Modeling application was undertaken to estimate the non-use values provided under different management options. Implicit prices for environmental attributes including the area of environmental forest protected, the number of bird species protected and the recreation use of the area were estimated. In addition, the implicit price of a social, non-marketed attributed, the employment of local people in wetland based extractive industries, was estimated. Compensating Surplus estimates for a number of alternative wetland management scenarios are also reported